The impact of different stages of lesson study on teachers' learning: the Bruneian context - Hj Suhaili, Hj Ade Shahren; Shahrill, Masitah; Hj. Mohd Yusof, Hajah Jamilah; Khalid, Madihah (The Sultan Hassanal Bolkiah Institute of Education, 2016)
This paper outlines on a study that investigated the impact of Lesson Study on Bruneian primary mathematics teachers' development in improving their instructional practices. Identification of 'critical events' that can influence the extent of teachers' learning which can promote the development of their instructional practices within the 3 stages of Lesson Study was the main purpose of the study. This paper shares the findings of a teachers' questionnaire of 28 primary mathematics teachers who have participated in the National Lesson Study Project in 2010. The questionnaire consisted of 17 items focusing on statements on teachers' perceptions in the three stages of Lesson Study and teachers were asked to designate their agreement on a 4-point scale which were (1) strongly agree, (2) agree, (3) disagree and (4) strongly disagree. Findings indicated that teachers' learning did took place in the 3 stages of lesson study, however the extent and the nature of their learning were different in each stage. Although the differences were not much but it is important to see which aspects of teachers' learning were 'dominant' in each of the 3 stages.